Living worship a multimedia resource for students and leaders - Caccamo, James F.; Johnson, Todd Eric, 1960-; Ruth, Lester, 1959- (Grand Rapids, MI : Brazos Press, 2010)
Living worship: Approximately 22 hours of video documenting eighteen months in the worship of Ravenswood Covenant Church in Chicago. DVD includes: covering church service, planning meetings, interviews, and expert commentary; more than 450 pages worth of text; over 400 images documenting the history of the church; a glossary of theology terms; essays covering topics central to congregational worship life; and, orders of worship reaching back 50 years. Speaking of worship: 90 minutes of interviews with outstanding teachers in homiletics, worship, music, the arts, and pastoral rites on vital issues and questions related to worship.
[Disc 1]. Living worship in theory and practice -- [disc 2]. Speaking of worship.
"Produced with assistance from the Calvin Institute of Christian Worship"--Container.
Keywords: Public worship; Liturgics